Dual-stage corrosion mechanisms and antibacterial enhancement of Cu-Sn-P alloys with Si and Al microalloying in simulated body fluid - Lin Su; Wenbin Liu; Yangfan Liu; Yanbin Jiang; Yanggang Wang; Zhou Li; Kaiyu You; ChuYu Wang; Gengyan Liu (Materials & Design)
The effects of P, Si and Al elements on the microstructure, corrosion properties and antibacterial properties of copper-tin alloys were studied. The addition of Si and Al elements reduced the layer fault energy of Cu-Sn-P alloy, refined grain and increased twins. Cu-Sn-P-Si and Cu-Sn-P-Al alloys were prone to grain boundary stripping corrosion and twin corrosion, which promoted the release of copper ions and improved the antibacterial properties. Cu-Sn-P-Al alloy had the best antibacterial activity. These results provide theoretical guidance for the development of new antibacterial copper alloy materials by microalloying the corrosion and ion release behavior of copper alloys.